A tethered bond / Siti Faridah Kamaruddin and Dayang Hummida Abang Abdul Rahman - Kamaruddin, Siti Faridah; Abang Abdul Rahman, Dayang Hummida (Corporate Communication Unit, UiTM Mukah Campus, 2024)
I'm trying to figure out why it is that I want to talk to you about my issue right now. I sometimes feel like I want to say something when I see you in front of me, but I'm worried no one would listen. Something prevents me from voicing my opinions. I can only convey something through this letter that I am unable to describe in words. Miss, Do you recall the time we worked on "The Ways to Build a Close Relationship between Teenagers and Family Members" as a writing exercise? Do you still recall that I asked you to come to my table after you chastised me for daydreaming, and all I said was "Nothing" when you finally arrived at my table?